2018
DOI: 10.1002/aic.16111
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the impact of SG1 disproportionation and the addition of styrene in NMP of methyl methacrylate

Abstract: A kinetic modeling study is presented for batch nitroxide mediated polymerization (NMP) of methyl methacrylate (MMA; nitroxide: N‐tert‐butyl‐N‐[1‐diethylphosphono‐(2,2‐dimethylpropyl)] (SG1)). Arrhenius parameters for SG1 disproportionation (A = 1.4 107 L mol−1 s−1; Ea = 23 kJ mol−1) are reported, based on homopolymerization data accounting for unavoidable temperature variations with increasing time, that is, nonisothermicity. For low targeted chain lengths (TCLs ≤ 300), this nonisothermicity is also relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…[31][32][33][34][35][36] Furthermore, the older kinetic models typically rely on more basic deterministic techniques 37,38 aiming understandably only at the prediction of the monomer conversion and average molecular properties, specifically average chain lengths. 39 However, even "simple" polymers such as PMMA [39][40][41] are distributed with respect to chain length, while the synthesis is characterized by side reactions and chain length dependent reactivities caused by a interplay of chemistry and diffusional limitations. 42,43 Hence, one needs to solve a very high amount of strongly coupled differential equations to deterministically describe the kinetics of populations of macromolecule types.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36] Furthermore, the older kinetic models typically rely on more basic deterministic techniques 37,38 aiming understandably only at the prediction of the monomer conversion and average molecular properties, specifically average chain lengths. 39 However, even "simple" polymers such as PMMA [39][40][41] are distributed with respect to chain length, while the synthesis is characterized by side reactions and chain length dependent reactivities caused by a interplay of chemistry and diffusional limitations. 42,43 Hence, one needs to solve a very high amount of strongly coupled differential equations to deterministically describe the kinetics of populations of macromolecule types.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, the main focus is on feedstock recycling of PMMA products originating from FRP of MMA in bulk. FRP of MMA follows a typical chain-growth mechanism involving in essence four consecutive types of chemical reactions, i.e., dissociation, chain initiation, propagation and termination, augmented by side reactions, such as chain transfer to monomer [ 41 , 42 , 43 ]. The propagation rate is many orders of magnitude larger than the dissociation, chain initiation and termination rate, the latter rates being similarly low thereby leading to a quasi-steady state for the concentration of the macroradicals.…”
Section: Radical and Anionic Polymerization Reaction Mechanisms Fomentioning
confidence: 99%
“…36,37 However, Gigmes et al and D'hooge et al reported the numerical simulation of dispersity for NMP using the PREDICI package and the kMC method, respectively, demonstrating that termination influences polymer dispersities. 38,39 In this work, a set of general dispersity equations for NMP is presented, reflecting the effect of termination on the Đ for NMP in the case of both first-order and power-law kinetic behaviors. The derivation is conducted by a model-based monodispersed polymer blending strategy, which is inspired by a widely used experimental approach for tailoring the dispersity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing explicit and user-friendly dispersity equations as a ready-to-use tool for the prevalent RDRP systems is desirable. Several years ago, Goto and Fukuda derived a simple analytical equation for dispersity in an ideal NMP system as well as other RDRPs without termination, predicting a monotonic decrease of dispersity with conversion. , However, Gigmes et al and D’hooge et al reported the numerical simulation of dispersity for NMP using the PREDICI package and the kMC method, respectively, demonstrating that termination influences polymer dispersities. , …”
Section: Introductionmentioning
confidence: 99%